Practical steps toward integrating economic, social and institutional elements in fisheries policy and management. (2nd May 2017) - Stephenson, Robert L.; Benson, Ashleen J.; Brooks, Kate; Charles, Anthony; Degnbol, Poul; Dichmont, Catherine M.; Kraan, Marloes; Pascoe, Sean; Paul, Stacey D.; Rindorf, Anna; Wiber, Melanie
Abstract: While international agreements and legislation call for incorporation of four pillars of sustainability, the social (including cultural), economic and institutional aspects (the 'human dimension') have been relatively neglected to date. Three key impediments have been identified: a relative lack of explicit social, economic and institutional objectives; a general lack of process (frameworks, governance) for routine integration of all four pillars of sustainability; and a bias towards biological considerations. Practical integration requires a 'systems' approach with explicit consideration of strategic and operational aspects of management; multidisciplinary or transdisciplinary evaluations; practical objectives for the four pillars of sustainability; appropriate participation; and a governance system that is able to integrate these diverse considerations in management. We challenge all involved in fisheries to immediately take five practical steps toward integrating ecological, economic, social and institutional aspects: (1) Adopt the perspective of the fishery as a 'system' with interacting natural, human and management elements; (2) Be aware of both strategic and operational aspects of fisheries assessment and management; (3) Articulate overarching objectives that incorporate all four pillars of sustainability; (4) Encourage appropriate (and diverse) disciplinary participation in all aspects of research, evaluation and management; and (5) Encourage development of (or emulate) participatory governance.